EFFECT OF NON- SURGICAL PERIODONTAL TREATMENT ON GLYCEMIC CONTROL AMONG TYPE 2 DIABETES MELLITUS PATIENTS WITH PERIODONTITIS - Salman, Sadia; Khan, Khurshid; Salman, Fariha; Hameed, Maliha (Journal of Ayub Medical College Abbottabad, 2016)
Background: Periodontitis and Diabetes Mellitus are two closely, bidirectional linked disease where periodontitis is a well-known complication of diabetes it is also considered to be a cause for poor glycaemic control. The present study objective was to evaluate the glycaemic control in patients suffering from both Diabetes Mellitus and Periodontitis after non-surgical periodontal treatment. Methods: A comparative cross-sectional study was conducted with two groups of patients attending Diabetic Clinic, Jinnah Hospital, Lahore, during six months from September 2013 to February 2014. Forty-six diabetes mellitus subjects who were undergoing non-surgical treatment of periodontal disease that includes mechanical removal of supra- and sub gingival bacterial plaque with scalers, antibiotics and or root canal if required while 46 subjects with diabetic mellitus having periodontal disease did not had treatment for periodontal disease. HbA1c was compared at base line and at three months. Data was compiled and analysed through SPSS version 16. Quantitative variables like HbA1c was presented as mean±SD. Qualitative variables like gender, education status, economic status, treatment for diabetes mellitus and periodontal disease were described by using frequency percentages. The t-test was applied to assess statistical significance in mean difference HbA1c between two groups. p-value <0.05 was considered significant. Results: Forty-six subjects who received non-surgical treatment for periodontitis 43 (93.5%) received scaling only while 3 (6.5%) received scaling plus antibiotics. Fall in the level of HbA1c was observed among subjects with treatment of periodontal disease indicating a good control of diabetes while in group without treatment there was either no change or increase in HbA1c. Mean HbA1c at baseline in group with treatment of periodontitis at baseline was 7.672±.6414 and without treatment was 6.957±.3494. (t= -1.008, p<.279). Mean HbA1c after 3 months in group with treatment of periodontitis was 6.867±.6168, and in group without treatment was 6.983±.3678. (t=6.641, p<.000). Conclusion: Non-surgical periodontal treatment is associated with improved glycaemic control (reduced HbA1c level) in type 2 diabetic patients. Keywords: Diabetes mellitus; periodontitis; Dental Hygiene